Reading the signs of the times. Design of a communal discernment practice in Catholic schools - van der Zee, Theo (International studies in Catholic education, 2025)
Societal developments and phenomena such as diversity, secularisation, individualisation and the marketisation of education challenge Catholic schools in their striving for good education. Issues related to these developments and phenomena put their distinctive articulation and interpretation of values and ethical commitments to the test. It is by no means easy for Catholic schools to take on these challenges and decide what to do regarding their educational endeavour. By taking an educational design perspective, this article aims to contribute to the issue of how Catholic schools act by presenting an intervention for communal discernment. Through reading the signs of the times, looking inwards, deliberating and then coming to decisions, Catholic schools will be able to take on the challenges and continue purposefully in their striving for good education. Based on an academic study of Christian spirituality, a generic design for a communal discernment practice is presented, consisting of four clusters of strategies for action, and reflective questions to activate these strategies. Suggestions for further research are included.